The big auto plant [videorecording (DVD)] - VanDerKloot, William; Duke, Tyler; Gillespie, Evan; Gillespie, Ryan (Big adventure series (Little Mammoth Media (Firm)), 2003)
Children will learn how an engine works, and see all the thousands of parts that go into a new car.